Experimental Investigation of Innovative Internal Trailing Edge Cooling Configurations with Pentagonal Arrangement and Elliptic Pin Fin - L. Tarchi; B. Facchini; S. Zecchi (International Journal of Rotating Machinery)
This paper describes a heat transfer experimental study of four different internal trailing edge cooling configurations based on pin fin schemes. The aim of the study is the comparison between innovative configurations and standard ones. So, a circular pin fin configuration with an innovative pentagonal scheme is compared to a standard staggered scheme, while two elliptic pin fin configurations are compared to each other turning the ellipse from the streamwise to the spanwise direction. For each configuration, heat transfer and pressure loss measurements were made keeping the Mach number fixed at 0.3 and varying the Reynolds number from 9000 to 27000. In order to investigate the overall behavior of both endwall and pedestals, heat transfer measurements are performed using a combined transient technique. Over the endwall surface, the classic transient technique with thermochromic liquid crystals allows the measurement of a detailed heat transfer coefficient (HTC) map. Pin fins are made of high thermal conductivity material, and an inverse data reduction method based on a finite element code allows to evaluate the mean HTC of each pin fin. Results show that the pentagonal arrangement generates a nonuniform HTC distribution over the endwall surface, while, in terms of average values, it is equivalent to the staggered configuration. On the contrary, the HTC map of the two elliptic configurations is similar, but the spanwise arrangement generates higher heat transfer coefficients and pressure losses.